1959
DOI: 10.1152/ajplegacy.1959.197.2.441
|View full text |Cite
|
Sign up to set email alerts
|

Alternative mechanism of cardiac acceleration in Bainbridge's infusion experiments

Abstract: Intravenous infusions on intact dog hearts both in closed- and open-chest experiments indicate that a rise in the intra-atrial pressure is accompanied by either a positive, a negative or a no chronotropic effect, irrespective of the integrity of vagi. Positive chronotropic effects of similar intensity were also obtained even after bilateral vagotomy, topical application of cocaine or parenteral administration of atropine, tetraethylammonium or hexamethonium compounds. Moreover, the rise in the intra-atrial pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1964
1964
1988
1988

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The manner in which the pacemaker cells are influenced by stretch to change their frequency is not clear, though some investigators claim that the pacemaker frequency may be primarily dependent on the tension in the pacemaker cells (PATHAK, 1959;JAMES and NADEAU, 1963).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The manner in which the pacemaker cells are influenced by stretch to change their frequency is not clear, though some investigators claim that the pacemaker frequency may be primarily dependent on the tension in the pacemaker cells (PATHAK, 1959;JAMES and NADEAU, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that distension of mammalian atrial tissues including the sinoatrial (SA) node produces an acceleration of heart rate (BAINBRIDGE,1915;SASSA and MIYAZAKI, 1920;SCHERF et al, 1949;HOLLANDER and WEBS, 1955;BLINKS, 1956;PATHAK, 1959) which appears to be due to a direct action on the pacemaker cells. Brooks and his coworkers LANGE et al, 1966) studied the effect of stretch on the discharge rate of in situ or isolated mammalian SA nodal region and suggested that the stretch-induced acceleration of pacemaker activity is mediated by a lowering of membrane potential caused by an increase in Na permeability, while extrinsic nerves are not essential to this reaction.…”
mentioning
confidence: 99%
“…For example, we found that heart rate still increased with volume loading after simple beta-receptor blockade but not after combined beta-receptor and cholinergic blockade or after cholinergic blockade alone. Although it has been suggested that volume loading induces a direct positive chronotropic effect (18)(19)(20), the data obtained in the present study in the dogs studied several days after recovery from bilateral vagotomy indicate that this mechanism, if present, must be minor, since heart rate failed to rise with volume loading in these dogs even though control rates were only 114 ± 3 beats/min, a level considerably less than that observed with either moderate volume loading (148 ± 1 1 beats/min) or maximum volume loading (178 ± 5 beats/min) in the intact conscious dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of postvagal tachycardia in the isolated heart preparation of the rabbit excludes the possibility that this cardioacceleration is due, in the intact animal, to the mechanical stretch of sinu-atrial node pace-maker cells by an increase in right atrial pressure during and after vagal stimulation (McDowall, 1956;Pathak, 1959).…”
Section: Discussionmentioning
confidence: 99%